Essays on culture, institutions, and development - LIU, Meng (Institutional Knowledge at Singapore Management University, 2023)
This dissertation consists of three chapters that study culture, institutions, and economic development. In the first chapter, we study the impact of Confucianism on long-run development in northern Vietnam. Using the variation in Confucian literati across 217 historical districts between the Primitive Le and Nguyen dynasties (1426 CE - 1919 CE), we find that districts with greater exposure to Confucianism have experienced better economic outcomes over the past century. The result is robust to using the distance to exogenously located hermit Confucian as an instrument and accounting for a battery of confounders. We show that the positive effects of Confucianism work through the persistence of the culture of diligence, respect for education, and group cohesion. The second chapter attempts to uncover the origin of long-term orientation (LTO) by exploiting the variation in historical exposure to natural disasters. We combine data on significant natural disasters occurring during 4360 BC -1980 CE with LTO data derived from multiple waves of the World Values Survey and European Values Survey. We test two opposing hypotheses borrowed from psychology. We find robust evidence at the individual, subnational, and country levels in favor of the view that a larger exposure to catastrophic events increases the degree of LTO. The third chapter examines the cultural impact of One Child Policy (OCP). Research has shown that OCP could change many family decisions. Such changes may consequently alter the incentives to preserve culture. To test this, we use the fines for unsanctioned births as the source of variations in OCP enforcement exposure and combine it with Population Census and survey data. Our results show that individuals whose mothers were subject to stricter OCP enforcement tended to have fewer siblings, receive higher levels of education, and develop closer relationships with parents. These higher-exposure individuals also show stronger family ties and more similar cultural values with their parents.